The impact of all-inclusive oﬀerings in a tourism destination’s competitiveness - Aleix Calveras Maristany; Jenny De Freitas (Investigaciones Regionales - Journal of Regional Research)
This study analyzes the impact of all-inclusive oﬀerings on a destination's competitiveness. When the rise in all-inclusive oﬀerings causes a negative externality on complementary services, it creates a market-size eﬀect. This results in an excessive supply of all-inclusive oﬀerings in the market. Imposing diﬀerent taxes on all-inclusive and non-all-inclusive oﬀerings is more eﬀective than a cap on the supply of all-inclusive oﬀerings. Taxes can implement the optimal allocation. We expect the market-size eﬀect to be harmful to competitiveness in mature destinations.